Dynamics of Contiguous Destitute Areas in China from 2000 to 2020 and the Risk of Returning to Poverty - Ge Zhai; Jiang Wu; Maoxin Zhang; Cifang Wu; Tingting He (Land)
Contiguous destitute areas (CDAs) in China, characterized by deep poverty and difficulty in alleviating it, have garnered attention for their spatial–temporal development. Using nighttime light (NTL) data from 2000 to 2020, we developed a novel method to identify spatiotemporal changes in CDAs. This is the first classification method based on multi-period continuous threshold judgement to objectively classify counties into expansion, shrinkage, or stability types, and quantify the intensity and ratio of these changes. The results showed that: (1) From 2000 to 2020, 345 counties expanded, 176 remained stable, and 11 shrank, accounting for 64.85%, 33.08%, and 1.07%, respectively. Dabie Mountains (VI), Luoxiao Mountains (XI), and Wuling Mountains (VII) had higher proportions of expanding counties, while shrinkage was concentrated in Tsinling-Daba mountains (V), VII, Lvliang Mountains (III), and Rocky Desertification Area (X). (2) The peak of expansions occurred between 2008 and 2011. (3) Both expansion and shrinkage intensities and ratios were generally low, with strong expansion primarily in IV and VI. We also found that there is the risk of returning to poverty in the development of the CDAs, such as space shrinking, lack of development impetus, coexisting expansion and shrinkage, and low intensity. It provides reference information for China’s future targeted and sustained poverty reduction policies and systems.